The Current Status of Mesenchymal Stromal Cells: Controversies, Unresolved Issues and Some Promising Solutions to Improve Their Therapeutic Efficacy - García-Bernal, David; García-Arranz, Mariano; Yáñez, Rosa M.; Hervás-Salcedo, Rosario; Cortés, Alfonso; Fernández-García, María; Hernando-Rodríguez, Miriam; Quintana-Bustamante, Óscar; Bueren, Juan A.; García-Olmo, Damián; Moraleda, Jose M.; Segovia, José C.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stromal cells (MSCs) currently constitute the most frequently used cell type in advanced therapies with different purposes, most of which are related with inflammatory processes. Although the therapeutic efficacy of these cells has been clearly demonstrated in different disease animal models and in numerous human phase I/II clinical trials, only very few phase III trials using MSCs have demonstrated the expected potential therapeutic benefit. On the other hand, numerous controversial issues on the biology and clinical applications of MSCs, including their specific phenotype, the need of an inflammatory environment to induce immunosuppression, the relevance of the cell dose and schedule, the cell delivery route (intravascular/systemic vs local cell delivery), and the selected cell product (i.e., use of autologous vs allogeneic MSCs, freshly cultured vs frozen and thawed MSCs, MSCs vs MSC-derived extracellular vesicles, etc) persist. In the current review article, we have addressed these issues with special emphasis in the new approaches to improve the properties and functional capabilities of MSCs after distinct cell bioengineering strategies.